Hematoma Expansion in Intracerebral Hemorrhage: An Update on Prediction and Treatment - Li, Zhifang; You, Mingfeng; Long, Chunnan; Bi, Rentang; Xu, Haoqiang; He, Quanwei; Hu, Bo (Frontiers in Neurology, 2020)
Intracerebral hemorrhage (ICH) is the most lethal stroke in the world, however there is no specific treatment to date. After years of effort, neurologists have found that hematoma expansion (HE) is a vital and avertable predictor of poor prognosis in ICH patients, with a not uncommon incidence ranging widely from 13% to 38%. Herein, the progress of studies on HE after ICH in recent years have been updated, and the topics of definition, prevalence, risk factors, prediction score models, mechanisms, treatment and prospect of HE are covered in this review. The risk factors and prediction score models, including clinical, imaging and laboratory characteristics, are elaborated in detail, but limited by sensitivity, specificity and inconvenience to clinical practice. The management of HE is also well discussed from bench work to bed practice. However, the upmost problem at present is that there is no treatment of HE proven to definitely improve the clinical outcomes. Thus, previous studies of HE bring drawn to the ICH patients, but further studies are needed to identity more accurate predictors and effective treatment in order to reduce HE.